The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1111/1467-9582.00061
|View full text |Cite
|
Sign up to set email alerts
|

Relating gender errors to morphosyntax and lexicon in advanced French interlanguage

Abstract: An correlational analysis between accuracy levels of gender agreement ± based on an analysis of 519 gender errors out of 9378 modifiers in the advanced French interlanguage of 27 Flemish L1 speakers-and morphosyntactic and lexical variables, revealed a clear negative relationship between the number of gender errors and fluency variables. No relation was found between gender errors and other types of agreement errors. This suggests that more advanced learners, whose interlanguage speech production process is mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
6

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 4 publications
1
10
0
6
Order By: Relevance
“…Although Spanish has a binary gender system (masculine or feminine) for nouns, determiners, adjectives, and pronouns (Roca, 1989), only nouns have intrinsic gender (Carroll, 1989; DeWaele & Véronique, 2000, 2001). For animate nouns, gender may be assigned conceptually and allow for determining the biological sex of the referent (natural or semantic gender; but not always; cf.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Spanish has a binary gender system (masculine or feminine) for nouns, determiners, adjectives, and pronouns (Roca, 1989), only nouns have intrinsic gender (Carroll, 1989; DeWaele & Véronique, 2000, 2001). For animate nouns, gender may be assigned conceptually and allow for determining the biological sex of the referent (natural or semantic gender; but not always; cf.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Anglophone learners of L2 Spanish initially transfer L1 properties (no gender on determiners or adjectives and no agreement) but may reset nominal features to L2 values, eventually gaining gender on determiners and adjectives with agreement. For example, Bruhn de Garavito and White (2002) reported that beginning and intermediate French‐Spanish late learners were highly accurate at producing determiner‐noun gender and number agreement, and White et al (2004) found that intermediate and advanced French‐Spanish and English‐Spanish late learners were as accurate as native Spanish speakers on perceiving and producing gender and number agreement in Spanish DPs (for further evidence that learners produce the same errors independently of their L1, see Bartning, 2000; Dewaele & Véronique, 2000, 2001; Fernández‐García, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a lot of research on both the comprehension and production of L2 grammatical gender (Andersen, 1984;Rogers, 1984;1987;Finneman, 1992;Shelton, 1996;Myles, 1995;Hawkins, 1998;Dewaele and Véronique, 2000;Franceschina, 2001;2002;White et al, 2004). These studies have shown that L2 gender errors are frequent, that overgeneralization to one form occurs, that accuracy depends on the actual amount of use of the L2 and not on the amount of classroom exposure and that gender agreement seems to be more difficult when the agreeing element is structurally more distant from the noun it has to agree with.…”
Section: Introductionmentioning
confidence: 99%
“…Ils doivent pour cela probablement vaincre une certaine réticence à utiliser des variantes sociolinguistiqes condamnées comme non-standard et faiblement marquées par le professeur de langue. Les extravertis semblent avoir un léger avantage, étant par nature moins anxieux et plus loquaces que les introvertis et ambivertis.L'effet plus important de la fréquence d'interactions authentiques, comparée à la durée et l'intensité de l'instruction formelle, a également été constaté dans des études sur l'acquisition de la compétence grammaticale des mêmes apprenants (Dewaele et Véronique, 2000; Dewaele, à paraître a).Nous avons suggéré que la grande variation inter-individuelle dans les taux d'omission est essentiellement due à l'interaction de variables socio-psychologiques, situationnelles et communicatives. Une partie beaucoup plus limitée dans la variaiton pourrait s'expliquer par la réapparition momentanée de structures non-natives fossilisées qui côtoyeraient ainsi occasionnellement les structures natives.…”
unclassified